Construction of Loop Polyzwitterion Brushes on PET Sheets via the Chain-End Closure Strategy To Improve Antifouling and Hemocompatible Properties - Ge, Zhaoyan (Langmuir : the ACS journal of surfaces and colloids, 2025)
Steric stabilization and lubrication give loop polymer brushes enhanced antifouling properties. In the study, linear zwitterionic poly(NMASMCMS) brushes were first constructed on a poly(ethylene terephthalate) (PET) surface through surface-initiated reversible addition-fragmentation chain-transfer (SI-RAFT) polymerization. The tethered linear brushes on sheets were then thiolated with ethanolamine, followed by oxidation to form loop brushes. The chain-end closure strategy to form loop brushes is facile, with a high transformation rate. The physical and chemical structures were characterized by the water contact angle (WCA), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM). Loop brush grafted sheets (PET-L) exhibited better lubricity than linear brush grafted sheets (PET-B) due to the rigidity of loop brush structures. The two brushes exhibited good antifouling and hemocompatible properties on low protein adsorption, bacteria adhesion, platelet adhesion, and hemolysis. In comparison, loop brushes performed with antifouling properties superior to those of linear brushes